The Social Structure of Participants of the Battle of Tewkesbury on May 4, 1471 - Andrey G. Prazdnikov (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2018)
The research object is the social structure of participants of the Battle of Tewkesberry on May 4, 1471. The purpose is to study the connections between participants and their role models in the times of social political crisis widely referred to as the Wars of the Roses. The research is based on prosopographic method and the sources containing the participants’ names. The sources include The Pastons’ Letters, official Parliamentary Rolls, narratives of John Bennet, chronicles of Tewkesberry Abbey, History of the Arrival of Edward IV, chronicles of John Warkworth and Polydore Virgil’s English History. After a great deal of extensive reading on the subject, 113 people have been listed, including 67 Lancasters and 46 Yorks. 80 of them are noblemen, knights and squires. However, there are some other noblemen (14), clerics, burghers and others. The sources containing personal data on the participants (mostly on the basis of Patent Rolls and Fine Rolls) helped to restore their biographies. A number of family relations and matrimonial ties between the participants have been revealed, liege – vassal relationships. Three models of social behavior have been revealed in the present research. Less than 1/5 of them are the loyal Lancasterians and Yorkists, who supported their camps in earlier years. The biggest group (75 %) consists of people who fought for their lords only once. They just did their duty and were unwilling to be exiled or outcast. Only 4 participants of the battle changed their political views, so the treason was an unlikely behavior during the period of the Wars of the Roses.